PROBLEMATIKA IMPLEMENTASI KURIKULUM MERDEKA MATA PELAJARAN PAI KELAS X DI MA PESANTREN PEMBANGUNAN MAJENANG KABUPATEN CILACAP - Irhamni, Muhammad; Wanojaleni, Kartika (MAMBA'UL 'ULUM, 2024)
The background of this research is the implementation of the independent curriculum in class X religious subjects at the Majenang Development Islamic Senior High School Islamic Boarding School. The independent curriculum is a new curriculum initiated by the Ministry of Education and Culture in February 2022. The MA Majenang Development Islamic Boarding School is a Madrasah that has implemented an independent curriculum based on Decree No. B-1775/DJ.I/Dt.I.I/PP.00/07/2022 concerning the implementation of the independent curriculum in madrasas. An independent curriculum creates flexible learning and gives freedom to institutions, students and educators in determining learning methods. Which is the learning process according to the interest of students. His type of research is field research with a qualitative descriptive approach. The subjects of this study were the head of the madrasah, deputy head of curriculum and teacher of religious subjects. The object of this research is the problematic implementation of the independent curriculum in religious subjects. The data collection methods used are observation, interviews, and documentation. Data analysis techniques used in the form of data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of the independent curriculum aims to complement the previous curriculum, namely the 2013 curriculum. The implementation of the independent curriculum at the Majenang Development MA Islamic Boarding School has been running although it is still gradual and has several problems. From the results obtained in this study there are several points contained in the implementation of the independent curriculum : ratory stage, implementation stage and evaluation stage. In addition, the implementation of the independent curriculum also has several problems, namely : problems with teaching staff, problems with madrasas and student problems.